Pedagogical intentions in university teaching (Impetus, 2024)
The aim was to understand the intentionalities that teachers imprint on their teaching and the contents they teach in professional training. It was approached from the phenomenology of practice. The sample consisted of 12 teachers from the Universidad del Quindío. The results emphasize the way in which the teacher agencies the knowledge of the professional careers, at the same time that he adds in the work of deepening the values and principles of the human being; he notices the development of skills for life and new forms of social integration. The components that make up the intentionality behind teaching are recognized: comprehensive training, the teacher's actions as lessons for future professionals and the educational relationship as the basis of the teacher's action.
Keywords: training; teachers; pedagogy; teaching; higher education